An in vitro investigation of a newer intracanal medicament Nisin on Enterococcus faecalis in comparison with chlorhexidine and calcium hydroxide - Suneel Kumar Chinni; Ashok Baskaran Veni; Manali R Srinivasan; Indra Rajamani (Wolters Kluwer Medknow Publications, 2011)
Aim: To determine the antibacterial efficacy of Nisin in comparison with Calcium hydroxide and Chlorhexidine. Materials and Methods: Fifty extracted lower premolar single-rooted teeth were collected and were instrumented with K3 rotary files. Then, root canals were inoculated with a bacterial solution of Enterococcus faecalis. After 21 days, the canals were inoculated with Saline, Nisin, Vancomycin, Calcium hydroxide, and Chlorhexidine. The roots were left for 7 days and on the 8 th day, to investigate the degree of infection of the radicular dentin, specimens of the dentin chips from the full length of the root canal were harvested using a sterile rotary K3 instrument (size 25 6% taper). Results: The results of the present study showed that Nisin and Chlorhexidine showed none of Colony Forming Units (CFU) in their respective group. Conclusion: Within the limits of the study, Nisin was effective in eradicating E. faecalis cells in pure culture and root canal dentin.